Implementasi Kebijakan Pendaftaran Tanah Sistematis Lengkap (PTSL) Di Desa Gilang, Kecamatan Taman, Kabupaten Sidoarjo - Syailendra Wahyu Pamungkas; Rachmawati Novaria; Adi Soesiantoro (Yayasan Cendekia Gagayunan Indonesia, 2024)
Land is very important for the life and economy of every human being. In Indonesia, the relaxation of land certification poses legal threats to owners. The PTSL program aims to provide legal clarity through certification, increase protection and facilitate easier access to services and land rights. However, implementation faces challenges, such as slow and complicated procedures, as seen in Gilang Village, Sidoarjo. This research aims to identify and analyze the implementation of PTSL policies in Gilang Village using a qualitative case study approach and purposive sampling. The results show that despite challenges in consistent communication and distribution of information, the PTSL program was overall successful. However, there are a few obstacles due to the use of existing resources and the high commitment of implementers. Improving communication and information management can increase program effectiveness in the future. The PTSL program has been implemented well in accordance with Minister of Agrarian Regulation Number 12 of 2017, with achievements in resources, disposition and bureaucratic structure. However, the main obstacle is communication, miscommunication between program implementers and the Gilang Village community causes confusion and dissatisfaction. The lack of effective communication media during the socialization process also hampers the process.